Developing of Hots Test Instruments in Computer-Based Exams on Rotational Dynamics and Rigid Bodies - Yunus Agustian; Neng Nenden Mulyaningsih; Dandan Luhur Saraswati (JPP (Jurnal Pendidikan dan Pembelajaran), 2021)
Higher-Order Thinking Skills (HOTS) based questions can train students to develop their reasoning power. Therefore, this study aimed to obtain a HOTS-based test instrument in a feasible computer-based exam on the topic of rotational dynamics and rigid body balance. The research method used in this development research is 4-D, consisting of four stages: define, design, develop, and disseminate. The result of this research is the HOTS-based test instrument in a computer-based test that is feasible on the material of rotational dynamics and rigid body balance that meets the validity requirements of material experts and media experts with the lowest V index value of 0.58 and the highest V index value equal to 0.83. The average percentage of the total validation score of material experts obtained were 77.78%, and media experts were 79.44%. Overall, the test instrument has a total media validation score of 78.61%, so that the computer-based HOTS test instrument with testing based on rotational dynamics and rigid body balance is categorized as valid and ready to use.